A systematic review of the literature describing the outcomes of near-peer mentoring programs for first year medical students - Akinla, Olawunmi; Hagan, Pamela; Atiomo, William (BioMed Central, 2018)
Background Transition into higher education has been identified as one of the most stressful periods for learners. Interventions targeting the transition phase such as near- peer mentoring might help address some of these challenges. We were however unable to identify a published systematic review of the literature describing outcomes of near-peer mentoring of medical students during the transition phase into medical school. The aim of this paper is to review the literature and describe the outcomes of near-peer mentoring schemes for first-year medical students in the transition phase.